2023
DOI: 10.1039/d2me00181k
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide – poly(m-anthranilic acid)–poly(ε-caprolactone) electrospun composite nanofibers: fabrication and properties

Abstract: The inclusion of iron and carboxylic acid- functionalized polyaniline into polymeric polycaprolactone structures is expected to enhance the electron-donating ability which in turn increases the compound conductivity and may induce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…All three aminobenzoic acid isomers (with the COOH group being positioned either ortho, meta, or para with respect to the amino group) have been used as copolymers in PANI systems [74,91,92]. In the case of the 4-aminobenzoic acid (4ABA) isomer, the COOH group blocks the 4-position, thereby impeding head-to-tail coupling, and would be expected to force ortho coupling, which would lead to a much more sterically complex polymer structure, as indicated in Figure 5.…”
Section: Polymerization Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…All three aminobenzoic acid isomers (with the COOH group being positioned either ortho, meta, or para with respect to the amino group) have been used as copolymers in PANI systems [74,91,92]. In the case of the 4-aminobenzoic acid (4ABA) isomer, the COOH group blocks the 4-position, thereby impeding head-to-tail coupling, and would be expected to force ortho coupling, which would lead to a much more sterically complex polymer structure, as indicated in Figure 5.…”
Section: Polymerization Mechanismmentioning
confidence: 99%
“…Benyoucef et al (2005) found that the meta derivative was more difficult to oxidize than the ortho and was associated with a greater degree of chain branching and shorter chains [24]. The structural consequences of ortho and meta anthranilic acid, however, have yet to be fully clarified [74,91]. 2016) employed 4-aminobenzoic acid not as a homopolymer but rather as an electropolymerizable end cap, which was added to a hyperbranched aliphatic polyester.…”
Section: Polymerization Mechanismmentioning
confidence: 99%
See 1 more Smart Citation